Exploring the human handwriting process - Bouslama, Faouzi; Benrejeb, Mohamed (Zielona Góra: Uniwersytet Zielonogórski)
The study of human handwriting movements is of great interest to researchers and biologists. It can lead to an understanding of the properties of the biological system that generates the human handwriting movements. With the identification of a dynamical system that exhibits characteristics similar to the biological one, it is possible to study handwriting movements, to identify their driving motor signals and to try to reproduce by machine the handwriting motion.
Keywords: human handwriting; hand-muscle system; EMG signals; Van der Gon dynamic models; feedback error learning